A mechanism to explain the creep behavior of gypsum plaster - Schug, Benedikt; Mandel, Karl; Schottner, Gerhard; Shmeliov, Aleksey; Nicolosi, Valeria; Baese, Rauno; Pietschniann, Bernd; Blebl, Markus; Sextl, Gerhard (Cement and Concrete Research, 2017)
Gypsum plaster is a widely used building material, as it is inexpensive and mechanically strong. However, the main disadvantage of gypsum is its significant loss of mechanical strength in a humid environment. As a result for instance gypsum wallboards bend when exposed to humidity. Despite intense research on this topic, the origin of the mechanisms that ultimately cause this deformation of bulk gypsum, i.e., the creep of gypsum is not yet thoroughly understood. In this work, the creep of gypsum is reviewed with fundamentally new experimental design approaches and modern analytical methods. The surface reactions of calcium sulfate dihydrate crystals are related to the macroscopic behavior of polycrystalline gypsum. The acquired data supports a model for moisture-triggered, pressure solution creep as the fundamental mechanism for the deformation of gypsum under mechanic load in a moist atmosphere.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Calcium sulfate dihydrate; Gypsum; Pressure solution creep; Sag; Solubility